FACILITY MANAGEMENT TO ENHANCE THE LEARNING PROCESS AT ELEMENTARY SCHOOLS IN SETIA DISTRICT - Armiadi Armiadi; Niswanto; Ismail (CV. RADJA PUBLIKA, 2024)
Elementary schools need personnel (school principals, teachers, administrative staff, security guards, and librarians), facilities (textbooks, teacher manuals, library books, teaching aids, office supplies, and furniture), infrastructure (land, buildings, libraries, and sports fields), and costs (school operational costs, building procurement costs, educational equipment costs, and book procurement costs). This study aims to determine: (1) Planning, procurement, utilization, maintenance, and elimination of educational facilities in Setia District Elementary Schools. Data collection methods include observation, interviews, and documentary studies. The results show the importance of educational facility and infrastructure management as support for learning activities. Detailed planning is required for the procurement of facilities and infrastructure that are in line with needs and field conditions. Educational facilities and infrastructure should be utilized effectively and efficiently to support the education process. Maintenance of facilities and infrastructure should also be done regularly to keep them in good condition. Damaged items should be reported to be replaced promptly with new ones.